An Analysis of Teachers Strategy and Students Reading Activity in Indonesian Secondary Education Using Merdeka Curriculum - Komalasari, Komalasari; Munir, Munir; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research aims to determine the used of teachers strategy in teaching English and students reading activity in Indonesian secondary education using merdeka curriculum class VIII.  This research used the method of qualitative descriptive with total samples of this study are 2 teachers and 8 students that consist of 4 students in different class, with 2 female and 2 male in classroom. This research using purposive sampling method. In this research, data collection was carried out by interview protocol. The results of the data analysis show that the teachers in teaching English used the strategy DRA, KWL, SQ4R and QRA. In addition, the students reading activity in classroom are the students was order to analyze the each of the body paragraph on their book besides students was order to analyze the descriptive text. This can be proven by methods of triangulation data methods in classroom learning material. Keywords:   Reading Strategy, DRA, KWL, SQ4R, QRA, Reading Activity.